The importance of nucleotide size in the chemistry and biology of DNA - Kool, Eric (Henry Stewart Talks, 2008)
Chemical and biophysical properties of size-expanded DNA bases (xDNA), Structure of xDNA, Design of benzo-widened DNA bases (yDNA), Non-polar nucleoside isosteres, Base pair replication without hydrogen bonds, Base analogues with systematically varied size, Steric effects in DNA replication in vitro and in vivo
Updated at 2020/12/22